Structural analysis and transport properties of [010]-tilt grain boundaries in Fe(Se,Te) - Kazumasa Iida; Yoshihiro Yamauchi; Takafumi Hatano; Kai Walter; Bernhard Holzapfel; Jens Hänisch; Zimeng Guo; Hongye Gao; Haoshan Shi; Shinnosuke Tokuta; Satoshi Hata; Akiyasu Yamamoto; et al. (Science and Technology of Advanced Materials)
Understanding the nature of grain boundaries is a prerequisite for fabricating high-performance superconducting bulks and wires. For iron-based superconductors [e.g. Ba(Fe,Co)2As2, Fe(Se,Te), and NdFeAs(O,F)], the dependence of the critical current density [Formula: see text] on misorientation angle ([Formula: see text]) has been explored on [001]-tilt grain boundaries, but no data for other types of orientations have been reported. Here, we report on the structural and transport properties of Fe(Se,Te) grown on CeO2-buffered symmetric [010]-tilt roof-type SrTiO3 bicrystal substrates by pulsed laser deposition. X-ray diffraction and transmission electron microscopy revealed that [Formula: see text] of Fe(Se,Te) was smaller whereas [Formula: see text] of CeO2 was larger than that of the substrate. The difference in [Formula: see text] between the CeO2 buffer layer and the substrate is getting larger with increasing [Formula: see text]. For [Formula: see text] of the substrates, [Formula: see text] of Fe(Se,Te) was zero, whereas [Formula: see text] of CeO2 was continuously increasing. The inclined growth of CeO2 can be explained by the geometrical coherency model. The [Formula: see text]-axis growth of Fe(Se,Te) for [Formula: see text] of the substrates is due to the domain matching epitaxy on (221) planes of CeO2. Electrical transport measurements confirmed no reduction of inter-grain [Formula: see text] for [Formula: see text], indicative of strong coupling between the grains.